Early adolescents' physical activity and nutrition beliefs and behaviours. Issue 1 (31st December 2022) - Hawks, Miranda; Bratton, Angela; Mobley, Sandra; Barnes, Vernon; Weiss, Steven; Zadinsky, Julie
ABSTRACT: Obesity in early adolescents is a public health concern and presents a risk for poor health outcomes later in life. Early adolescents' beliefs and behaviours of physical activity and healthy eating are not well understood. The purpose of this ethnographic inquiry was to explore the physical activity and healthy eating beliefs and behaviours of early adolescents (n = 15) who attended a community organization in an urban cluster in the Southeastern USA. Data from semi-structured interviews, participant observations and artefact collection were analysed using constant comparative analysis. We learned that five main influences on the early adolescents' healthy eating and physical activity included recognizing benefits of physical activity and healthy eating, family influences, connecting with the community, peer influences, and developing a sense of self. Findings highlight community influences on early adolescents' physical activity and healthy eating beliefs and behaviours that should be taken into account when developing health promotion strategies.